Work-family Balance in Textile Industries of Tamil Nadu - P Sankar, Jayendira; Yoganandham, G.; John, Jeena Ann (International Journal of Psychosocial Rehabilitation, 2020)
This study is conducted to examine the relationship between workplace factors and work-family balance towards the selected textile industries. The independent variables of this study include work role, workload, and management practices; the dependent variable is work-family balance. A total of 400 respondents from 4 different textile industries (100 Ammayappar Textile Private Limited, 100 Stanfab Apparels Private Limited, 100 Sri Kanyaka Garments Private Limited, and 100 Regency International Clothing Private Limited). To assess the relationship between the effect of workplace factors towards the employee's work-family balance of selected textile industries. The workplace factors include a) work role, b) workload and c) management practices. The work-family balance measured by a) current work role, b) current workload, c) management interest, d) work personal life, e) time spent at work, and f) worry about work. The researcher used random sampling, mean, standard deviation, and regression analysis. The output of the analysis is there is a relationship between the independent variables (workplace factors (work role, workload, and management practices)) and dependent variable (relationship towards employee work-family balance of selected companies in the Thiruvallur district). The respondents are highly satisfied with the time spent on work, this proves that the workplace factor has a direct and high relationship on the work-family balance.  KEYWORDS: ,  ,